Soluble CD83 Triggers Resolution of Arthritis and Sustained Inflammation Control in IDO Dependent Manner - Royzman, Dmytro; Andreev, Darja; Stich, Lena; Rauh, Manfred; Bäuerle, Tobias; Ellmann, Stephan; Boon, Louis; Kindermann, Markus; Peckert, Katrin; Bozec, Aline; Schett, Georg; Steinkasserer, Alexander; et al. (Frontiers in Immunology, 2019)
Interference with autoimmune-mediated cytokine production is a key yet poorly developed approach to treat autoimmune diseases such as rheumatoid arthritis. Herein, we show that soluble CD83 (sCD83) enhances the resolution of autoimmune antigen induced arthritis (AIA) by strongly reducing the expression levels of cytokines such as IL-17A, IFNγ, IL-6, TNFα and IL-1β within the joints. Noteworthy, also the expression of RANKL, osteoclast differentiation and joint destruction was significantly inhibited by sCD83. Enhanced resolution of arthritis by sCD83 was mechanistically based on IDO, since inhibition of IDO by 1-methyltryptophan completely abrogated sCD83 effects on AIA. Blocking experiments, using anti-TGF-β antibodies further revealed that also TGF-β is mechanistically involved in the sCD83 induced reduction of bone destruction and cartilage damage as well as enhanced resolution of inflammation. Resolution of arthritis was associated with increased numbers of regulatory T cells, which are induced in a sCD83-IDO-TGF-β dependent manner. Taken together, sCD83 represents an interesting approach for down-regulating cytokine production, inducing regulatory T cells and inducing resolution of autoimmune arthritis.